THE EVOLUTIONARY PROCESSES OF THE STRUCTURE OF EDUCATION POLYTECHNICS - Анна Геннадьевна Сошина (Sovremennoe Stroitelʹstvo i Arhitektura, 2018)
This article is an analysis of the evolution of the formation of the polytechnics. Reveal the principles of formation of institutions and their units. It must be emphasized, that in the period of active construction of polytechnics of the Soviet period is marked accumulation of difficulties in organizing the educational process and the deterioration of the general condition training Wednesday.